Analysis of The Role of Indonesian Sharia Bank Certificates In Controlling The Liquidity of Sharia Banks - Nur Chotami Putra Muslim; Mugiyati, Mugiyati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to describe and analyze the role of the Sharia Bank Indonesia Certificate (SBIS) in controlling the liquidity of Sharia banking in Indonesia. The research method employed is qualitative with a literature review approach, sourcing data from various relevant references. The primary focus of this study is on the liquidity management of Sharia banking, utilizing data from national journals indexed by Google Scholar and Sinta. The findings indicate that SBIS plays a crucial role in the liquidity risk management of Sharia banking operations. Sharia banks invest their funds in SBIS to mitigate liquidity challenges, leveraging this instrument to avoid potential financial strain. The study demonstrates that SBIS can significantly enhance the stability and resilience of the Sharia banking sector. This is particularly evident when SBIS is integrated into a bank’s overall liquidity risk management strategy, complemented by efficient monitoring and evaluation mechanisms. Consequently, SBIS is established as a vital instrument for Sharia banks to maintain liquidity equilibrium, ensuring more stable and sustainable banking operations. The study underscores the importance of SBIS in reinforcing the financial health of Sharia banks, advocating for its strategic incorporation to bolster overall banking stability